Analysis Analysis Of Training Effect On Employee Performance Through Employee Retention To The Employee of PT. Perkebunan Nusantara XII Kertowono Garden: Analisis Pengaruh Training Terhadap Employee Performance Melalui Employee Retention Pada Pegawai PT. Perkebunan Nusantara XII Kebun Kertowono - Zhafirah Ayudo; Budiono (Profesional Muda Cendekia Publishing, 2023)
This research aims to explain how training impacts Employee Performance through Employee Retention at the main office and Afdeling puring employees of PT. Perkebunan Nusantara XII Kertowono Garden. Using quantitative research, a saturation sampling technique, and a questionnaire to collect data from 67 employees as respondents. This research was processed by using the SmartPLS 3.0 software. The results of the study revealed that training has a positive and significant effect on Employee Performance. Training variable on Employee Retention also has a positive and significant impact. The Employee Retention variable on Employee performance had no positive effect. Then, the Employee Retention variable cannot mediate Training on Employee Performance.